Adhesion behaviour of bulk supramolecular polymers via pillar[5]arene-based molecular recognition. Issue 98 (23rd November 2021) - Lai, Jinlei; Huang, Shiyu; Wu, Shuanggen; Li, Fenfang; Dong, Shengyi
Abstract : Pillar[5]arene–acid-based supramolecular adhesives with tough adhesion performances on different substrates were obtained. Abstract : Pillar[ n ]arenes were rarely used as the building blocks for supramolecular adhesives. Herein, pillar[5]arene-based supramolecular polymer materials with tough adhesion behaviours on different substrates were prepared, with adhesion strengths up to 4.75 MPa. Strong and long-term dichloromethane-resistant adhesion performances were successfully obtained.